From strings to things. Issue 1 (8th February 2016) - Fox, Robert
Abstract : Purpose: – This paper aims to explore current developments in the semantic Web and the role libraries can play in exposing institutional and bibliographic content using linked data and unique identifier systems. Design/methodology/approach: – This is a regular journal column. Findings: – There are many ways in which libraries can contribute to the scholarly community through the description as well as traditional authority control work flow to integrate research and bibliographic content with the larger semantic Web. Originality/value: – The theory behind linked data is commencing to have a more pronounced impact on the way the Web operates. Major players including publishers and commercial entities are contributing to the semantic Web through partnerships with the wider Internet community as well as data providers such as Universities. Given the open nature of many of these systems as well as consortial participation, this is an opportune time for libraries to contribute to these efforts in service of their constituencies.